Anatomical localization and stereoisomeric composition of Tribolium castaneum aggregation pheromones - Yujie, Lu; Beeman, Richard W.; Campbell, James F.; Park, Yoonseong; Aikins, Michael J.; Mori, Kenji; Akasaka, Kazuaki; Tamogami, Shigeyuki; Phillips, Thomas W. (My University, 2011)
We report that the abdominal epidermis and associated tissues are the predominant sources of male-produced pheromones in the red flour beetle, Tribolium castaneum and, for the first time, describe the stereoisomeric composition of the natural blend of isomers of the aggregation pheromone 4,8-dimethyldecanal (DMD) in this important pest species. Quantitative analyses via gas chromatography–mass spectrometry showed that the average amount of DMD released daily by single feeding males of T. castaneum was 878 ± 72 ng (SE). Analysis of different body parts identified the abdominal epidermis as the major source of aggregation pheromone; the thorax was a minor source, while no DMD was detectable in the head. No internal organs or obvious male-specific glands were associated with pheromone deposition. Complete separation of all four stereoisomers of DMD was achieved following oxidation to the corresponding acid, derivatization with (1R, 2R)- and (1S, 2S)-2-(anthracene-2,3-dicarboximido)cyclohexanol to diastereomeric esters, and their separation on reversed-phase high-performance liquid chromatography at −54°C. Analysis of the hexane eluate from Porapak-Q-collected volatiles from feeding males revealed the presence of all four isomers (4R,8R)/(4R,8S)/(4S,8R)/(4S,8S) at a ratio of approximately 4:4:1:1. A walking orientation bioassay in a wind tunnel with various blends of the four synthetic isomers further indicated that the attractive potency of the reconstituted natural blend of 4:4:1:1 was equivalent to that of the natural pheromone and greater than that of the 1:1 blend of (4R,8R)/(4R,8S) used in commercial lures.
Citation: Lu,Y., Beeman, R.W., Campbell, J.F., Park, Y., Aikins, M.J., Mori, K., …Phillips, T.W. (2011). Anatomical localization and stereoisomeric composition of Tribolium castaneum aggregation pheromones. Retrieved from http://krex.ksu.edu
Keywords: Chirality; 4,8-Dimethyldecanal; Insect; Red flour beetle; Tribolium; Chemical ecology; Stored grain